Kajian Kerja Penyelenggaraan bagi Rumah Keluarga Angkatan Tentera Malaysia di Kuala Lumpur - Goh, Kai Chen; Anis Suraya, Amaludin; Asrul Nasid, Masrom; Norliana, Sarpin; Gui, Hun Chuen (UTHM Publisher, 2023)
Maintenance work on buildings has become a responsibility for those who have experience in the field by using various facilities and advanced technology. Government buildings such as the high-rise housing of the Malaysian Army Forces Family House need attention because the building was built a long time ago, in the 70s. The population that lives in the area with an average of over 1000 residents. There are three objectives for this study which are to examine the maintenance methods found in the Malaysian Army Forces Family Homes in Kuala Lumpur, identify the problems found in the Malaysian Army Forces Family Homes and determine the appropriate measures to improve maintenance in the Malaysian Army Forces Family Homes Malaysia. This study focuses on the old building of the Malaysian Army Forces Family House located in Kuala Lumpur. The interview method is used to be done in the study area. There were 5 respondents in this study, which consisted of the housing unit management of the Malaysian Army Forces Family House and residents of the RKAT residence. Nevertheless, some suggestions are also presented in improving maintenance. The findings of the study obtained are such as effective maintenance acceleration from the authorities and the use of quality goods being one of the factors in the maintenance carried out so that durability can be maintained.